Silício oriundo da cinza de casca de arroz carbonizada como promotor do rendimento e da qualidade fisiológica de sementes de soja - Oliveira, Sandro de (2013)
Soybean is an important crop for Brazilian agriculture. The use of quality seeds, as well as appropriate plant nutrition and the adoption of modern techniques of cultivation are fundamental to the success of the crop. The use of silicon is a clean technology to environmentally and in addition may offer several benefits to plants. The aims of this study were to evaluate the effect of application of silicon from carbonized rice husk through the seed treatment and from soil in two soybean cultivars, and evaluate physiological quality of treated seeds, morphologic characteristics, yield components, yield and physiological quality of the seed produced. Four experiments were performed in randomized complete block design, using carbonized rice husk as a source of silicon. The experiments differ as the application form of carbonized rice husk and five doses of silicon were applied using seed coating (0, 30, 60, 90, and 120 g 100 kg seed-1) and throught soil were used the following doses (0, 1, 2, 3, and 4 tons ha-1). The soybean cultivars used in this study were (BMX Turbo RR and NA 5909 RR). Physiological quality of treated seeds and seed produced were evaluated by germination test and vigor tests. Morphological characteristics and yield components were also analyzed. The results showed that the application rates of silicon in the soil increases productivity, than when applied as seed treatment. The physiological quality of the seeds of the cultivar BMX Turbo RR is influenced positively with increasing doses of silicon. The thousand seed weight is positively influenced by the application of silicon levels in the cultivars used, and can increase productivity. Seed treatment cultivar NA 5909 RR increases the length shoots of seedlings originated from seeds treated and produced. The application of silicon levels in the soil provides an increase in yield per plant cultivar BMX Turbo RR.